Macrophages: emerging targets for ulcerative colitis - Chen, Siqing; Qin, Zhang; Lin, Xiaoyuan; Zhou, Sainan; Xu, Yin; Zhu, Ying (Frontiers in Immunology, 2025)
BackgroundUlcerative colitis (UC) is a chronic inflammatory bowel (IBD) disease characterized by a complex pathogenesis and limited treatment options. Macrophages play a key role in the pathophysiology of UC by regulating inflammatory responses and tissue repair processes. Currently, there is no comprehensive summary of macrophage regulatory pathways in UC, either domestically or internationally.ObjectiveThis review aims to systematically elucidate the role of macrophages in UC and their specific regulatory mechanisms, and to identify potential therapeutic strategies and future research directions.MethodsA comprehensive literature review was conducted, integrating recent advances from global studies to explore macrophage-related pathways and functional alterations in UC. Special attention was given to studies investigating molecular mechanisms underlying macrophage polarization and function.ResultsEvidence indicates that macrophage dysfunction is a central mechanism in the pathogenesis of UC. Major findings demonstrate that metabolic reprogramming serves as a fundamental pathway inducing phenotypic and functional alterations in macrophages. Additional mechanisms mediating these changes include epigenetic modifications, chemokine-driven recruitment, microbial metabolite induction, autophagy, and apoptosis. Multiple drugs targeting macrophages have shown effectiveness in treating UC.ConclusionTargeting macrophage-related pathways represents an effective therapeutic approach for UC. This review provides a theoretical foundation for developing precision treatments focused on macrophage modulation and highlights important new avenues for future research.